The Impact of Perception of Justice on Tax Compliance Behavior through the Mediating Role of Social Support: An Empirical Study in Pakistan (Journal of Social Sciences Review, 2023)
The government adjusts its financial obligations and collects taxes to pay for the public through taxes. Tax behavior varies from individual to individual. Tax audits and fines are also policies to collect tax amounts. The study aims to determine tax compliance behavior. A quantitative approach is applied to obtain the respondent's perception of justice in tax laws. Overall total number of questionnaires sent to bar councils was 400, of which 325 lawyers responded. The problem is that Pakistan needs a better tax collection system; therefore, many problems are faced during tax collection. The justice system is better for recovering the tax penalties, whereas procedural justice investigates the compliance of individuals about the tax. Taxpayers also find ways to reduce the amount of tax and make deduction claims by hiding some of their assets. Tax audit is also a significant field to assess and measure fraud in the tax collection system. Results differentiate that there is a positive and significant relationship between tax compliance behavior and perception of justice. So, it rejects the null hypothesis and shows a significant relationship. If the individuals cooperate with the government and perform their duties well, then the structure of the tax system can survive and collaborate in the economy of Pakistan.
Keywords: Perception on Justice; Social Support; Tax Compliance Behavior; Tax Laws; Deterrence Theory; Pakistan